Ryanodine receptor mediated calcium release contributes to ferroptosis induced in primary hippocampal neurons by GPX4 inhibition - Gleitze, Silvia; Ramirez, Omar; Vega-Vásquez, Ignacio; Yan, Jing; Lobos, Pedro; Bading, Hilmar; Núñez, Marco T.; Paula-Lima, Andrea; Hidalgo, Cecilia (Antioxidants, 2023)
Ferroptosis, a newly described form of regulated cell death, is characterized by the iron-dependent accumulation of lipid peroxides, glutathione depletion, mitochondrial alterations, and enhanced lipoxygenase activity. Inhibition of glutathione peroxidase 4 (GPX4), a key intracellular antioxidant regulator, promotes ferroptosis in different cell types. Scant information is available on GPX4-induced ferroptosis in hippocampal neurons. Moreover, the role of calcium (Ca2+) signaling in ferroptosis remains elusive. Here, we report that RSL3, a selective inhibitor of GPX4, caused dendritic damage, lipid peroxidation, and induced cell death in rat primary hippocampal neurons. Previous incubation with the ferroptosis inhibitors deferoxamine or ferrostatin-1 reduced these effects. Likewise, preincubation with micromolar concentrations of ryanodine, which prevent Ca2+ release mediated by Ryanodine Receptor (RyR) channels, partially protected against RSL3-induced cell death. Incubation with RSL3 for 24 h suppressed the cytoplasmic Ca2+ concentration increase induced by the RyR agonist caffeine or by the SERCA inhibitor thapsigargin and reduced hippocampal RyR2 protein content. The present results add to the current understanding of ferroptosis-induced neuronal cell death in the hippocampus and provide new information both on the role of RyR-mediated Ca2+ signals on this process and on the effects of GPX4 inhibition on endoplasmic reticulum calcium content.